2022
DOI: 10.3390/agronomy12010221
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Agricultural Soils with Long-Term Contamination of Arsenic and Copper in Two Chilean Mediterranean Areas

Abstract: Soil amendments may decrease trace element accumulation in vegetables, improving food security and allowing the recovery of contaminated farmlands. Despite some promising results in the laboratory, validation of soil amendments in field conditions are scarce, especially in aerobic soils. Here, we assessed the effect of different potential soil amendments on arsenic (As) accumulation in lettuces. Then, we compared them in terms of food security and the associated investment (efficacy and efficiency, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Another 16 studies assessed the biological or ecological impacts of the contaminations, including mainly plants and earthworms (e.g., Mondaca et al, 2017; Vivas et al, 2022), while five studies assessed the human health risks (e.g., Berasaluce et al, 2019). On the other hand, 16 studies focused on remediation alternatives for degraded landscapes (e.g., Pardo et al, 2018) or agricultural uses (Carvajal et al, 2023; Mondaca et al, 2022). Other studies focused on developing chemical methods or social issues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another 16 studies assessed the biological or ecological impacts of the contaminations, including mainly plants and earthworms (e.g., Mondaca et al, 2017; Vivas et al, 2022), while five studies assessed the human health risks (e.g., Berasaluce et al, 2019). On the other hand, 16 studies focused on remediation alternatives for degraded landscapes (e.g., Pardo et al, 2018) or agricultural uses (Carvajal et al, 2023; Mondaca et al, 2022). Other studies focused on developing chemical methods or social issues.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the potential use of biological solutions using Trichoderma has also been reported (Carvajal et al, 2023). On the other hand, it has been proven that applying soil amendments can improve food security by decreasing As accumulation in lettuce (Mondaca et al, 2022). Nevertheless, despite validating some low‐cost remediation technologies in the study area, the lack of a scientific study with a broader perspective hampers the land restoration process.…”
Section: Introductionmentioning
confidence: 99%
“…Mondaca et al (2022) validated the remediation effects of several soil amendments, including diammonium phosphate (DP), iron sulfate (IS), ferrous phosphate (FP), calcium peroxide (CP), and organic matter (OM), in contaminated sandy and loamy soils under field conditions (Figure 2F) [11]. The study found that phosphate amendments (DP and FP) reduced the foliar arsenic (As) concentration in lettuce grown in both areas, while CP only reduced it in the sandy soils.…”
Section: Remediation Of Agricultural Soils With Long-term Contaminati...mentioning
confidence: 99%
“…(E) Effects of different salt types and salt concentrations (0, 0.5%, 1.0%, 2%, 3%, and 3.5%) on the Cd desorption rates (%) [10]. (F) The geographical location of the studied areas and the main trace element sources: (a) sandy soils area; and (b) loamy soils area [11]. (G) Canonical scores of the first two canonical discriminant functions (Can) of the control and PLB treatments (1, 5, and 10 = 1%, 5%, and 10%) [12].…”
Section: Combination Of Biochar and Phosphorus Solubilizing Bacteria ...mentioning
confidence: 99%
“…Also, the role of agricultural activity in accelerating As contamination needs to be investigated, as a significant amount of As could be released from the sediments due to the agriculture activity and contaminate shallow groundwater resources, as in Bengal delta, India 213 . Work on As translocation in rice cultivation and its implication for human health by Bastías and Baldarrian 214 and recent work of Moncada et al 215 dealing with the remediation of agricultural soils with long-term As and Cu contamination are efforts towards filling this gap.…”
Section: Controlling Factors For As Pathwaysmentioning
confidence: 99%